Pregnancy-Associated Venous Thromboembolism: Insights from GARFIELD-VTE - Jerjes-Sánchez, Carlos; Rodriguez, David; Farjat, Alfredo E.; Kayani, Gloria; MacCallum, Peter; Lopes, Renato D.; Turpie, Alexander G.G.; Weitz, Jeffrey I.; Haas, Sylvia; Ageno, Walter; Goto, Shinya; Goldhaber, Samuel Z.; Angchaisuksiri, Pantep; Nielsen, Joern Dalsgaard; Schellong, Sebastian; Bounameaux, Henri; Mantovani, Lorenzo G.; Prandoni, Paolo; Kakkar, Ajay K.; on behalf of the GARFIELD-VTE investigators (TH Open, 2021)
Introduction The risk of venous thromboembolism (VTE) increases during pregnancy and the puerperium such that VTE is a leading cause of maternal mortality.Methods We describe the clinical characteristics, diagnostic strategies, treatment patterns, and outcomes of women with pregnancy-associated VTE (PA-VTE) enrolled in the Global Anticoagulant Registry in the FIELD (GARFIELD)-VTE. Women of childbearing age (<45 years) were stratified into those with PA-VTE (n = 183), which included pregnant patients and those within the puerperium, and those with nonpregnancy associated VTE (NPA-VTE; n = 1,187). Patients with PA-VTE were not stratified based upon the stage of pregnancy or puerperium.Results Women with PA-VTE were younger (30.5 vs. 34.8 years), less likely to have pulmonary embolism (PE) (19.7 vs. 32.3%) and more likely to have left-sided deep vein thrombosis (DVT) (73.9 vs. 54.8%) compared with those with NPA-VTE. The most common risk factors in PA-VTE patients were hospitalization (10.4%), previous surgery (10.4%), and family history of VTE (9.3%). DVT was typically diagnosed by compression ultrasonography (98.7%) and PE by chest computed tomography (75.0%). PA-VTE patients more often received parenteral (43.2 vs. 15.1%) or vitamin K antagonists (VKA) (9.3 vs. 7.6%) therapy alone. NPA-VTE patients more often received a DOAC alone (30.2 vs. 13.7%). The risk (hazard ratio [95% confidence interval]) of all-cause mortality (0.59 [0.18–1.98]), recurrent VTE (0.82 [0.34–1.94]), and major bleeding (1.13 [0.33–3.90]) were comparable between PA-VTE and NPA-VTE patients. Uterine bleeding was the most common complication in both groups.Conclusion VKAs or DOACs are widely used for treatment of PA-VTE despite limited evidence for their use in this population. Rates of clinical outcomes were comparable between groups.
Keywords: venous thromboembolism; registry; deep vein thrombosis; pulmonary embolism; pregnancy